Perempuan dan Pelacuran dalam Kumpulan Cerpen Genduk Dukuh Seti Karangan Rohana Handaningrum Sebuah Kajian Feminis Radikal - Laura Andri Retno Martini (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Prostitution or prostitution is a phenomenon in people's lives and is considered a "social problem". The general view states that the emergence of prostitution is based on a sense of women's helplessness in aspects of life when compared to men. This perception is not only found in social reality. The condition of women as objects also appears in literary works, as a reflection of people's perceptions. Therefore, it takes a study in the perspective of feminism, especially radical feminists to explore the issue of prostitution that occurs in women. The feminist literary criticism approach was carried out in this study with the type of qualitative research. Data was taken from the collection of Genduk Dukuh Seti short stories written by Rohana Handaningrum. The study was conducted aimed at describing the elements of radical feminism found in texts. The results of this study indicate that there are elements of radical feminism in the cepen group. The power relations of men and women are shown in the doctrine of marriage and the traditional ties that bound women. Whereas the removal of virginity and prostitution is a form of women's power over their bodies.